The LOM application profile for agricultural learning resources of the CGIAR. (2nd June 2009) - Zschocke, Thomas; Beniest, Jan; Paisley, Courtney; Najjar, Jehad; , Erik Duval
The international agricultural research centres of the CGIAR have established a repository for agricultural learning resources in collaboration with the ARIADNE Foundation. To make it easier to find these resources, an application profile, CG LOM Core, was developed on the basis of the IEEE Learning Object Metadata (LOM) standard. It defines the collection of metadata elements and value spaces drawn from other namespaces, adapted to the requirements of the CGIAR in describing and sharing their learning resources with an international audience. It maintains increased semantic interoperability within the CGIAR community and preserves compatibility with other repositories outside of the CGIAR.